ҚАРАҚАЛПАҚ АЙМАҒЫ ҚАЗАҚ АҚЫН-ЖЫРАЎЛАР МИЙРАСЫНЫҢ ПАЙДА БОЛЫЎ ХӘМ ҚӘЛИПЛЕСИЎИНДЕ ҚАРАҚАЛПАҚ ЭТНО-ФОЛЬКЛОРЛЫҚ АРЕАЛЫ ХӘМ ӘДЕБИЙ ОРТАЛЫҒЫНЫҢ ТУТҚАН ОРНЫ - Төрткулбаева, Т.; Алламбергенов, К.А. (SCIENCE and SOCIETY, 2016)
In the article there have been described the Karakalpak ethno-folklore and literary areal in the XIX-XX centuries. There is also shown its place in forming the heritage of Kazakh poets and bards on the territory of Karakalpakstan. The appearance and formation of ethno-folklore and literary heritage of Kazakh poets- bards was formed by the influence of Karakalpak folklore and literary environment with ancient national-literary roots.
Keywords: region of Karakalpakstan; heritage of Kazakh poets and bards; traditions and tutorship; national ethno-folklore literary environment; influence and literary-folklore relationship; jenres; forms in the heritage of Kazakh jiraus-akins on the territory of Karakalpakstan typology of creative and interpretative activities